PREBIOTICS AND THE GUT-BRAIN AXIS: IMPLICATIONS FOR COGNITIVE DEVELOPMENT IN EARLY CHILDHOOD - Pascaramadhani, Addini; Septiani, Seala; Kania R, Rahayu; Basrowi, Ray Wagiu; Sundjaya, Tonny (Journal of Indonesian Specialized Nutrition, 2025)
Background: Many factors influence cognitive development in early childhood, one of the latest is including gut health. Recent evidence places the role of a mediator of brain function on the part of the gut-brain axis, with nutrition overall and prebiotics specifically being imperative. Prebiotics stimulate selectively the grow of beneficial bacteria in the gut with potential implications on neurodevelopment. Methods: A narrative review that included peer-reviewed articles between 2010-2024 was conducted using PubMed, Scopus, and Google Scholar. Animal models and human clinical trials, both examining the impact of prebiotics on cognitive measures, were incorporated. Results: Prebiotics such as GOS, FOS, and resistant starch were found to increase the production of short-chain fatty acids, modulate the immune system, and excite neurotransmitter pathways. Clinical trials showed improved attentional ability and emotional control in prebiotic-supplemented formula-fed infants. Preclinical research showed enhanced memory and reduction in anxiety-like behaviors in animal models following ingestion of prebiotics. Conclusion: Prebiotics play a key role in cognitive development in early childhood through modulation of gut microbiota and neuroimmune signaling. Food-based prebiotics offer a sustainable approach to early brain development. Longitudinal studies are needed to demonstrate long-term benefits.